Investigate the Effect of Pre-drilling in Friction Drilling of A7075-T651 - Demir, Zulkuf; Ozek, Cebeli (Taylor & Francis Inc, 2014)
Friction drilling is a non-traditional hole achieving method that is a clean, chip-less process, which is called thermal drilling, form drilling, flow drilling, and friction stir drilling. In this study pre-drilling friction drilling was investigated for improving the bushing shape of A7075-T651, which is a brittle cast material. During the process, surface roughness and bushing shapes were analyzed and generated frictional heat was measured by the virtue of thermocouples. Experiments were carried out to 4mm and 6mm in thicknesses of A7075-T651 aluminum alloy at 1200, 1800, 2400, 3000, and 3600rpm spindle speeds, 20, 40, 60, 80, and 100mm/min feed rates with using high-speed steel rotating conical tool, whose diameter is 8mm. Consequently, the bushing shapes were advanced without cracks and petal formation in pre-drilling Friction drilling in comparison with without pre-drilling process. With increasing pre-drilled hole diameter the generated frictional heat was decreased. The achieved temperature was realized to be 1/2-1/3 of the melting temperature of the workpiece. Surface roughness values were decreased with decreasing or increasing both spindle speed and feed rate correspondingly.
Keywords: Pre-drilling; Roughness; Bushing; Temperature; Friction-drilling